Ability of TLR agonists to upregulate Brucella abortus strain RB51 mediated protection in a murine respiratory model - M Walker; N Sriranganathan; I Kanevsky; K Zimmerman; N Tenpenny; M Makris; S Werre; S Witonsky (Journal of Vaccines and Immunology - Peertechz Publications, 2019)
Brucella abortus is a Gram-negative intracellular zoonotic bacterium that causes infertility and abortion in cattle, and undulant fever in humans. Its low dose of infectivity, ability to be aerosolized, and ease of genetic modification, makes it a bioterror concern. The overall goal is to generate a safe and effective vaccine for humans. One candidate vaccine is Brucella abortus strain RB51, which was approved for use in cattle, and provides protection by initiating a strong T-helper 1 (CD4 Th1) response. Based on a model for aerosol exposure, mice were vaccinated intranasally (IN) with strain RB51 and challenged IN with B. abortus strain 2308. However, strain RB51 did not protect. Protection against Brucella is mediated through Toll Like Receptors (TLRs) 2, 4 and 9. The addition of TLR 2 or TLR 4, and a trend with TLR9 agonists, when combined with IN strain RB51 vaccination, significantly increased bacterial clearance in the lung after strain 2308 challenge. Therefore, for this study, we hypothesized that combining TLR agonists 2, 4, and 9 with strain RB51 IN would enhance protection and clearance in the lung against strain 2308 challenge (IN), by activating the DC1 and CD4 Th1 and CD8 immune response. This study showed that protection was not enhanced by combining all TLR agonists. The group with non-significantly greater clearance was strain RB51 and TLR 2 and 4 agonists. Additional studies are warranted to further define the differential mechanisms and endpoints of protection and chronic infection.